Acid functionalized carbons as catalyst for glycerol etherification with benzyl alcohol - Chiosso, María Eugenia (2020)
In this paper, the catalytic behaviour of two different carbonaceous systems, commercial carbon (Cc) and synthetic carbon (Cs) functionalized with concentrated sulfuric acid (–SO₃H) and with reduced aryl diazonium salt (–PhSO₃H), was studied in the etherification of glycerol (Gly) with benzyl alcohol (BA). The catalytic activity and selectivity were studied varying the catalyst percentage (5, 10 and 15 wt%) and the initial reactant mass ratio. Taking into account the results obtained, the experimental conditions selected to continue with the catalytic studies were: temperature 393 K, Gly:BA molar ratio 3:1 and a catalyst loading of 10 wt%. Mono- and diethers were the main products. For the Cc-based catalysts, higher conversion (66%) and selectivity (90%) were obtained with the most acidic system, Cc–PhSO₃H. Changing the carbon functionalization method (–PhSO₃H for –SO₃H groups) produced a considerable increase in glycerol conversion (from 23 to 66%) and in selectivity to ME + DE (from 62 to 90%). On the other hand, for both Cs-based systems a great increase in performance was obtained, about 95% conversion after 360 min of reaction. Monoether was the major product of the reaction with a selectivity of 79% for Cs–SO₃H and 87% for Cs–PhSO₃H, which was maintained with reuse. Etherification of glycerol (Gly) with benzyl alcohol (BA) with two carbonaceous systems synthesized in the laboratory and functionalized with –SO₃H and –PhSO₃H.